Phenotyping and identification of target traits for de novo domestication of wheat wild relatives - Zeibig, Frederike; Kilian, Benjamin; Özkan, Hakan; Pantha, Sumitra; Frei, Michael; Justus Liebig University Giessen (My University, 2023)
De novo domestication—the modification of domestication genes in crop wild relatives via genome editing—is an approach for harnessing the beneficial genetic diversity of crop wild relatives. A prerequisite for de novo domestication is phenotyping to identify genetic materials suitable for cultivation in the respective environment. Taxa from the wheat genepool (Triticum aestivum, Triticum durum, Triticum monococcum) are a staple food; these taxa comprise wild relatives of different ploidy levels. The diploid Triticum boeoticum and Triticum urartu and the tetraploid Triticum dicoccoides and Triticum araraticum harbor desirable traits such as high grain quality and abiotic and biotic stress tolerance. Hence, they are candidates for de novo domestication. Here, we grew 111 wild wheats and 38 landraces originating predominantly from the Fertile Crescent and six modern wheat cultivars in a field in Giessen, Germany, to evaluate their environmental adaptability to the central European climate and to identify potential candidates and target traits for de novo domestication. We demonstrate that several wild taxa are suitable for cultivation in the central European environment and that they have distinct characteristics that need to be modified during de novo domestication. The normalized difference vegetation index and the thermal time to heading and flowering indicated excellent adaptability of some wheat wild relatives to central European conditions. The values of yield parameters such as grain weight per plant, number of tillers, and thousand kernel weight were lower in the wild wheats than in the landraces. Therefore, these traits should be targeted for improvement during the de novo domestication of wild wheats.
Keywords: ddc:630